CEO compensation, change, and corporate strategy - Dow, James (2022)
CEO compensation can influence the kinds of strategies that firms adopt. We argue that performance-related compensation creates an incentive to look for overly ambitious, hard to implement strategies. At a cost, shareholders can curb this tendency by precommitting to a regime of CEO overcompensation in highly changeable environments. Alternatively shareholders can commit to low CEO pay, although this requires a commitment mechanism (either by the board of the individual company, or by the society as a whole) to counter the incentive to renegotiate upwards. We study the conditions under which the different policies for CEO compensation are preferred by shareholders.